Hydrogen bonding interactions and supramolecular networks of pyridine-aryl based thiosemicarbazides and their Zn(II) complexes - GUNNLAUGSSON, THORFINNUR; PANDURANGAN, KOMALA; MC CABE, THOMAS; KITCHEN, JOANNE (My University, 2013)
The synthesis of five pyridyl derived thiosemicarbazides, 1-5, is presented. All five were formed in a single step from 2-hydrazinopyridine with commercially available isothiocyanates using microwave assisted synthesis. Compounds 1-4 were structurally characterised by single crystal diffraction analysis, and showed extended supramolecular hydrogen bonding arrays. Furthermore, the Zn(ii) complexes 6 and 7 have been prepared using ligands 1 and 5, and structurally characterised, again showing elegant assemblies of metal-supramolecular structures with solvent accessible channels, demonstrating that these building units are excellent candidates for use in supramolecular chemistry and crystal engineering.
PUBLISHED
Keywords: supramolecular hydrogen bonding arrays; supramolecular hydrogen bonding arrays